O Uso de fontes histórias no ensino de história: práticas e desafios - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This research aims to analyze the way in which work with sources occurs in History classes at a State College located in the city of Ouro Verde de Goiás. Throughout the text, the importance of the discipline History for the training of students and the way in which the use of historical sources can awaken in them the ability to develop hypotheses and, consequently, a greater interest in historical themes. As a theoretical framework, we use the book entitled History Teaching fundamentals and methods, in which, Circe Maria Fernandes Bittencourt (2008) presents the transformation process that history teaching has undergone over time in Brazil, as well as the importance of using historical sources in the teaching of this discipline. The methodology used to carry out this research was the analysis of school documents that provide information about the dynamics of the classes, these being: the teacher's lesson plan; students' school activities and the Pedagogical Political Project of the school where the research was developed. In this methodological context, the “sources are presented in a diversified way, grouping, basically in: written, material, iconographic / visual or audiovisual and oral sources” (SANTANA, 2010, p. 126-127). As conclusions, the study leads to the impression that the freedom that the teacher gives students to analyze the documents awakens in their student audience the ability to raise questions and possible explanations for the historical facts.
The use of historical sources in history teaching : practices and challenges
Keywords: Fontes Históricas - Ensino de história; Fontes Históricas - Disciplinas Escolares - Curso de História; Historical Sources - Teaching; Historical Sources - School subjects; CIENCIAS HUMANAS::EDUCACAO